Penerapan Metode Case Based Reasoning untuk Mendiagnosa Penyakit Demensia - Elsa Risqi Amalia; Magdalena Simanjuntak; I Gusti Prahmana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Dementia is a growing global health challenge due to the aging population and lifestyle changes. Early and accurate diagnosis is crucial but often difficult and costly. The Case-Based Reasoning (CBR) method in artificial intelligence offers a solution by mimicking human problem-solving based on past experiences. This study aims to develop and implement an efficient and reliable CBR-based dementia diagnosis system. The system is expected to analyze and compare patient symptoms and medical histories with documented cases to provide faster and more accurate diagnostic recommendations. The implementation of CBR in a web-based expert system using PHP and MySQL has proven effective, significantly contributing to the improvement of patient quality of life and healthcare system effectiveness.